AB0332 Comorbidities prevalence and charlson index in a cohort of patients with rheumatoid arthritis. (12th June 2018) - Azuaga-Piñango, A.B.; Castellanos-Moreira, R.; Rodriguez-Garcia, S.C.; Mandelikova, S.; Frade-Sosa, B.; Diaz-Castillo, A.; Sapena, N.; Gonzalez-Delaurens, C.; Ruiz-Esquide, V.; Camacho, O.; Cuervo, A.; Ramirez, J.; et al.
Abstract : Background: The Charlson comorbidity index (CCI) is a prognostic scale, which gives a numerical value that indicates the burden of comorbidities in a patient. This index is obtained from the sum of 19 medical conditions that have been related to mortality and has been validated in several studies. Patients with rheumatoid arthritis (RA) are more at risk than the general population of developing comorbidities. However, these often go unnoticed despite the impact on the disease activity and to treatment response, as shown by different studies such as COMORA. Objectives: To determine the prevalence of comorbidities in a cohort of patients with RA and estimate CCI. Methods: Cross-sectional descriptive study, patients diagnosed with RA according to the EULAR/ ACR 2010 classification criteria were included. All patients were followed up in a rheumatology service in a tertiary hospital. Comorbidities were obtained from the medical records. To measure comorbidities, CCI was calculated, the diagnosis of RA was not included in the index. We defined three categories of comorbidity according to CCI: 0 (no comorbidity, applied to patients with no previous record of conditions included in the CCI), 1 to 2 (moderate) and 3 or more (severe). Others comorbidities not included in CCI, such as hypertension (HTN), dyslipidemias (DLP), thyroid disease (TD), osteoporosis (OP) were collected. Results: 130 patients (103 women) were analysed; mean age was 58.6±12.9 years and disease duration of 6.0±4.4 years. 82.8% were seropositive for rheumatoid factor (n: 83) and/or anti-CCP (n: 97). 44.6% had previous smoking history, 22 were current smokers. The most observed comorbidities in our cohort were: overweight and obesity (BMI ≥25; 63%), DLP (38.8%), HTN (31.5%), chronic kidney disease (32.3%; 6.9% ≥Stage III) and chronic lung disease (23.8%). Other diseases included TD (18.5%), OP (17.7%), diabetes mellitus (9.2%) and liver disease (9.2%). Five patients with a history of tumour (2 metastases) and 2 lymphomas in the last 5 years. Four patients had a heart disease, in 3 as an ischaemic event. According to CCI, 20.8% of the patients had a Charlson 0, 43.8% Charlson 1–2, and 35.4% Charlson ≥3. Conclusions: In our cohort, despite being a relatively young population, the presence of comorbidities and cardiovascular risk factors is relatively high, in agreement with what has been observed in other studies. 1 out of 3 patients has a severe comorbidity burden. Disclosure of Interest: None declared